Exploring Psychosocial Pressures and Their Impact on University Students’ Mental Wellbeing - Chhantel, Mamata; Shakya, Nasana (DAV Research Journal, 2025)
This study investigates the impact of academic, family, financial, and peer pressures (here we call them psychosocial pressure) on the mental wellbeing of university students in the Kathmandu Valley of Nepal. It further explores the demographic variations such as age, occupation, and gender in relation to wellbeing outcomes. A quantitative, cross-sectional design was employed with convenience sampling. Data were collected from 300 students across four universities in the Kathmandu Valley using a structured questionnaire based on validated scales. Responses were rated on a 5-point Likert scale. Reliability was confirmed through Cronbach’s alpha. Data analysis was conducted using SPSS, applying descriptive statistics, correlation, and regression analysis. Findings revealed that academic pressure had the strongest negative effect on mental wellbeing, followed by family, financial, and peer pressure. Collectively, these factors explained 52% of the variance in wellbeing. ANOVA showed significant differences across age groups and occupations, but t-tests found no significant gender-based differences. The study concludes that academic and family pressures are the most detrimental to student wellbeing, while financial and peer pressures also contribute negatively, though to a lesser extent. Universities must address these factors to improve students’ mental wellbeing. The findings highlight the need for institutional interventions, including academic counseling, family engagement programs, financial guidance, and structured peer-support initiatives. Policymakers and mental health practitioners could prioritize students’ wellbeing within higher education frameworks in Nepal. This research provides one of the empirical examinations of multiple psychosocial pressures on Nepali university student’s wellbeing.